حسين عباس سلمان بعض التغايرات الفسلجيه والنسيجيه في ذكور الجرذان المختبريه المعرضه لجرع مختلفه من المضاد الفطري Ketoconazole - عباسحسن (University of Thi-Qar Journal of Science, 2019)
This study was performance to investigate the effect of over doses(high dose and long term) of antifungal ketoconazole on body weight, liver weight, Biochemical parameters (ALP, AST and ALT enzymes, as well as total protein and cholesterol concentrations), and histological study of liver . For this purpose twenty adult male rats were divided randomly into equal four groups as below: Animals of control were treated with drinking water, first group (T1) treated with drinking water and 1.5mg/kg of body weight of ketoconazole, second group (T2) treated with drinking water and 3mg/kg of body weight of ketoconazole, third group(T3) treated with drinking water and 6mg/kg of body weight of ketoconazole, At the end of treatment, animalswere weighted, and anesthetized, blood draw was done to biochemical tests, then animals were sacrificed and dissected, after that liver, were eradication to weighted and prepared histological slide. The results revealed that the different concentrations of ketoconazole led to significant decrease (P<0.05) in body weight in T2 and T3 comparison with control group, and significant decrease in total protein and cholesterol concentrations in T3 comparison with control group. Where as significant increase (P<0.05) in liver weight in T3 and significant increase (P<0.05) in transamines enzymes (AST, ALT), Alkaline phosphate enzyme (ALP), in T1, T2 and T3 comparison with control group. The histopathological results revealed a necrotic and degenerative changes in liver cells caused by ketoconazole. It can be concluded that the effect of different doses of ketoconazole or using to long term led to negative effects on public health.